2005
DOI: 10.1128/jb.187.3.1022-1035.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Enterococcus faecalis SigV Protein Is an Extracytoplasmic Function Sigma Factor Contributing to Survival following Heat, Acid, and Ethanol Treatments

Abstract: Analysis of the genome sequence of Enterococcus faecalis allowed the identification of two genes whose protein products showed 33 and 34% identity with those of sigV and yrhM of Bacillus subtilis, respectively. These genes, named sigV and rsiV, are predicted to encode members of the extracytoplasmic function subfamily of eubacterial RNA polymerase sigma and anti-sigma factors, respectively. This group of sigma factors has been shown to regulate gene expression in response to stress conditions. sigV and rsiV we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 58 publications
7
68
0
1
Order By: Relevance
“…has not been fully described. Benachour et al (24) identified two genes (sigV and rsiV) in E. faecalis that are under the control of the same operon and are predicted to encode sigma and anti-sigma factors. Further analysis indicated the differential expression of the operon in response to exposure to various stresses; notably, it was overexpressed under conditions of glucose starvation and complete starvation, suggesting that it plays an important role in the response of enterococci to nutrient depletion (24).…”
Section: Responses To Environmental Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…has not been fully described. Benachour et al (24) identified two genes (sigV and rsiV) in E. faecalis that are under the control of the same operon and are predicted to encode sigma and anti-sigma factors. Further analysis indicated the differential expression of the operon in response to exposure to various stresses; notably, it was overexpressed under conditions of glucose starvation and complete starvation, suggesting that it plays an important role in the response of enterococci to nutrient depletion (24).…”
Section: Responses To Environmental Stressorsmentioning
confidence: 99%
“…Benachour et al (24) identified two genes (sigV and rsiV) in E. faecalis that are under the control of the same operon and are predicted to encode sigma and anti-sigma factors. Further analysis indicated the differential expression of the operon in response to exposure to various stresses; notably, it was overexpressed under conditions of glucose starvation and complete starvation, suggesting that it plays an important role in the response of enterococci to nutrient depletion (24). Another E. faecium regulatory protein ( 54 ) was suggested to be a potential virulence factor capable of influencing the rate of autolysis (and, by extension, the nature and composition of the biofilm matrix [173]) and governing sensitivity to certain bacteriocins (51,74).…”
Section: Responses To Environmental Stressorsmentioning
confidence: 99%
“…Eep confers resistance to other biological stressors. Benachour et al (4) showed that a sigV deletion mutant is attenuated compared to a wild type when subjected to high-temperature, low-pH, and ethanol stress conditions. Having established a link between Eep and SigV phenotypes for lysozyme resistance, we reasoned that other biological stresses known to impact a sigV mutant might also negatively affect an eep mutant compared to their effects on its isogenic parent.…”
Section: Deletion Of Eep Renders E Faecalis More Susceptible To Lysomentioning
confidence: 99%
“…pSV14 (P sigV -lacZ) and pVI16 (P pgdA -lacZ) were created by amplifying the promoter regions of sigV with primers SigVP1 and SigV2 and the pgdA promoter with primers PgdAP1 and PgdAP2. The promoter regions for both these plasmids were defined based on the known transcriptional start sites for both sigV and pgdA (4). These promoters contain the consensus SigV promoter recognition sequence (5= TGAAAC-N 17 -CGTC 3=), and we included an additional ϳ1-kb region (1,188 bp for sigV and 914 bp for pgdA) upstream from the transcriptional start site to provide additional genetic context for the promoter fusion studies.…”
mentioning
confidence: 99%
“…The recent availability of the E. faecalis V583 genome sequence (28) provides a tool for the identification of potential E. faecalis regulatory components, such as alternative sigma factors (2), transcriptional regulators (41,42), and two-component systems (6,17,25,37), that could be involved in the infection process.…”
mentioning
confidence: 99%